2009
DOI: 10.1002/pola.23749
|View full text |Cite
|
Sign up to set email alerts
|

A minimal amount of acrylonitrile turns the nitroxide‐mediated polymerization of methyl methacrylate into an almost ideal controlled/living system

Abstract: Nitroxide‐mediated controlled/living free‐radical polymerization of methyl methacrylate initiated by the SG1‐based alkoxyamine BlocBuilder was successfully performed in bulk at 80–99 °C with the help of a very small amount of acrylonitrile (AN, 2.2–8.8 mol %) as a comonomer. Well‐defined PMMA‐rich P(MMA‐co‐AN) copolymers were prepared with the number‐average molar mass, Mn, in the 6.1–32 kg mol−1 range and polydispersity indexes as low as 1.24. Incorporation of AN in the copolymers was demonstrated by 1H and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
142
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(151 citation statements)
references
References 63 publications
9
142
0
Order By: Relevance
“…The polymer is, in fact, a macroinitiator, which can be used to reinitiate the NMP process in the presence of a second monomer, thereby generating block copolymers 29,30 . However, if an end material is sought, the polymerisation thermodynamics might become unfavourable at high temperature as the importance of entropy rises accordingly 31 , which will induce depropagation processes 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…The polymer is, in fact, a macroinitiator, which can be used to reinitiate the NMP process in the presence of a second monomer, thereby generating block copolymers 29,30 . However, if an end material is sought, the polymerisation thermodynamics might become unfavourable at high temperature as the importance of entropy rises accordingly 31 , which will induce depropagation processes 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…[65] At 200 °C, 97.0% of the living SAN polymer remained, and 99.5% of the deactivated SAN remained. TGA also showed that 100.0% of the PE remained at 200 °C.…”
Section: Thermal Stability Of Polymersmentioning
confidence: 99%
“…[65] With the same set-up as described in the previous section, NHS-SAN copolymer °C. The AN molar composition of the SAN copolymer using FTIR was F AN = 0.43.…”
Section: Removal Of the Sg1 End-group From San Copolymer For Chain-enmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be an advantage for the synthesis of block copolymers as the polymerisation can be reinitiated in presence of a second monomer [9] . However, there is an interest in removing the nitroxide end-group, for example to improve thermal stability [17] or introduce functional groups [1,18,19] . Furthermore, there is a growing trend for combining different polymerisation methods for the synthesis of new copolymers, which cannot be obtained by one technique only [20][21][22] .…”
mentioning
confidence: 99%